Determination of lethal electric field threshold for pulsed field ablation in ex vivo perfused porcine and human hearts - Kos, Bor; Mattison, Lars; Ramirez, David; Cindrič, Helena; Sigg, Daniel C.; Iaizzo, Paul A.; Stewart, Mark T.; Miklavčič, Damijan (Frontiers in Cardiovascular Medicine, 2023)
Pulsed field ablation is an emerging modality for catheter-based cardiac ablation. The main mechanism of action is irreversible electroporation (IRE), a threshold-based phenomenon in which cells die after exposure to intense pulsed electric fields. Lethal electric field threshold for IRE is a tissue property that determines treatment feasibility and enables the development of new devices and therapeutic applications, but it is greatly dependent on the number of pulses and their duration. In the study, lesions were generated by applying IRE in porcine and human left ventricles using a pair of parallel needle electrodes at different voltages (500- 1500 V) and two different pulse waveforms: a proprietary biphasic waveform (Medtronic) and monophasic 48×100 μs pulses. The lethal electric field threshold, anisotropy ratio, and conductivity increase by electroporation were determined by numerical modeling, comparing the model outputs with segmented lesion images. The median threshold was 535 V/cm in porcine (N=51 lesions in n=6 hearts) and 416 V/cm in the human donor hearts (N=21 lesions in n=3 hearts) for the biphasic waveform. The median threshold value was 368 V/cm in porcine hearts (N=35 lesions in n=9 hearts) cm for 48×100 μs pulses. The values obtained are compared with an extensive literature review of published lethal electric field thresholds in other tissues and were found to be lower than most other tissues, except for skeletal muscle.